Comparative study on Rickettsia-like organisms in the midgut epithelial cells of different Glossina species - Shaw, M.K.; Moloo, S.K. (Cambridge University Press, 1991)
The midgut epithelium ofGlossina morsitans centralis, G. austeni, G. pallidipes, G. palpalis palpalis, G. p. gambiensis, G. fuscipes fuscipes, G. tachinoidesandG. brevipalpisfrom ILRAD-bred colonies was examined, by electron microscopy, for the presence and distribution of Rickettsia-like organisms (RLOs). RLOs were present in the midgut epithelial cells of all non-teneral tsetse. InG. m. centralis, G. pallidipesand, to a much lesser extent,G. brevipalpis, RLOs were numerous and were present in all the specimens examined. RLOs were present in fewer numbers in the epithelial cells of tenerals of these three tsetse species. In contrast, RLOs occurred in very much lower numbers within the midgut cells of nonteneralG. austeni, G. p. palpalis, G. p. gambiensis, G. f. fuscipesandG. tachinoides; were not seen in every specimen, and were rarely observed in the midgut cells of teneral tsetse. The RLOs were typical rod-shaped bacteria with an inner and outer membrane, which occurred free within the host cell cytoplasm and appeared to cause no obvious pathology. The micro-organisms divided by binary fission and at least two distinct morphological forms plus a range of intermediate forms were seen in the midgut cells. A comparison of the presence and numbers of RLOs within the midgut cells and the midgut infection rates of bothTrypanosoma congolenseandT. b. brucei, both betweenGlossinaspecies and also within the same stock of tsetse, clearly indicates that the ability of trypanosomes to establish and develop to mature infections is unlikely to be correlated solely with the presence of RLOs within the tsetse midgut.